Delegating home care for the elderly to external caregivers? An empirical study on Italian data - Matteo Lippi Bruni; Cristina Ugolini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
We study care arrangement decisions in Italy, where families are increasingly delegating the role of primary caregiver to external (paid) people also for the provision of home care. We consider a sample of households with a dependent elderly person cared for either at home or in a residential home, extracted from a survey representative of the population of Italy's Emilia-Romagna region. We investigate the determinants of a household's decision to opt for one of the following three alternatives: the institutionalisation of elderly family members, informal home care, or paid home care. We estimate two model specifications, based on a simultaneous and a sequential decision process respectively, the results of which are fairly consistent. Disability related variables, rather than family characteristics, emerge as the main determinants of institutionalisation. On the other hand, household characteristics and socio-economic variables are more influential when it comes to choosing between informal and formal home care provisions.
Keywords: C21; D13; I18; 330